Estrategias de enseñanza y su incidencia en el aprendizaje en la especialidad de soldadura eléctrica en los estudiantes del Centro de Formación Artesanal Balao cantón Balao, provincia del Guayas - Sánchez Gallegos, Gil Rogerio (2018)
The real research work entitled as a teaching strategy and its impact on learning in the specialty of electric welding in the students of the training center "Balao" Catón Balao, Province of Las Guayas. It was executed due to the urgent need to learn with the appropriate strategies for electric welding so that students obtain an excellent knowledge in electrical manipulation of electric welding so that they can develop with learning in the specialty of electric welding so that be more competitive to obtain the expected result and be able to cope with everyday life. Electric welding and its impact on learning is an art in which the student will put into practice their skills and knowledge in the institution for a better daily performance in their professional life and, at the same time, develops their creativity. By recording a quality observation of the correct use of electric welding, students have the theoretical and practical knowledge to improve the quality of teaching at the center of the craft phonation, of course, we must continue teaching with quality and warmth and have a positive result with the right strategies.